1995
DOI: 10.3109/00365529509089786
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cromolyn Sodium in Comparison with Elimination Diet in the Irritable Bowel Syndrome, Diarrheic Type Multicenter Study of 428 Patients

Abstract: These results confirm the high prevalence of adverse reactions to foods in diarrheic irritable bowel syndrome and the usefulness of cromolyn sodium treatment in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 20 publications
2
91
0
Order By: Relevance
“…Thus, our data pave the way for considering the release of these mediators as a potential mechanism contributing to IBS pathophysiology. However, our study has some limitations, and a number of issues remain to be addressed, including the assessment of: (1) mediators (other than histamine and tryptase) of mast cell and nonmast cell origin, which are likely involved in the activation of sensory neurons; (2) participation of mechanical stimuli on the sensitization of sensory fibers; (3) causes underlying the increased release of mucosal mediators involved in sensory neuron activation [eg, psychologic factors, neurohormonal factors (eg, neuropeptides, corticotrophin releasing factor) food allergens, intestinal microflora, intestinal permeability]; (4) potential clinical correlates between sensory neural pathways activation evoked by mucosal mediators and abdominal pain perceived by patients; (5) clinical usefulness of inhibition of mast cell activation (eg, mast cell stabilizers, 36,37 anti-IgE antibodies, 38 inhibitors of the intracellular protein tyrosine kinase, Syk 39 ), or antagonism of the effects of mast cell mediators (eg, histamine and proteases receptor antagonists). These still open issues could represent the objective of future ad hoc-designed studies.…”
Section: Mast Cell Mediators From Ibs Patients Excite Nociceptive Neumentioning
confidence: 99%
“…Thus, our data pave the way for considering the release of these mediators as a potential mechanism contributing to IBS pathophysiology. However, our study has some limitations, and a number of issues remain to be addressed, including the assessment of: (1) mediators (other than histamine and tryptase) of mast cell and nonmast cell origin, which are likely involved in the activation of sensory neurons; (2) participation of mechanical stimuli on the sensitization of sensory fibers; (3) causes underlying the increased release of mucosal mediators involved in sensory neuron activation [eg, psychologic factors, neurohormonal factors (eg, neuropeptides, corticotrophin releasing factor) food allergens, intestinal microflora, intestinal permeability]; (4) potential clinical correlates between sensory neural pathways activation evoked by mucosal mediators and abdominal pain perceived by patients; (5) clinical usefulness of inhibition of mast cell activation (eg, mast cell stabilizers, 36,37 anti-IgE antibodies, 38 inhibitors of the intracellular protein tyrosine kinase, Syk 39 ), or antagonism of the effects of mast cell mediators (eg, histamine and proteases receptor antagonists). These still open issues could represent the objective of future ad hoc-designed studies.…”
Section: Mast Cell Mediators From Ibs Patients Excite Nociceptive Neumentioning
confidence: 99%
“…Some of the abnormalities (clusters of contractions) resembled those described in patients with the irritable bowel syndrome (IBS) who, however, display a normal fed pattern (Kellow & Phillips, 1987); the other kinds of abnormalities (highamplitude jejunal waves, simultaneous activity fronts) have never been described in IBS patients. These ®ndings are interesting, since dietary mechanisms have been claimed in the pathogenesis of IBS (Alun Jones et al, 1982;Nanda et al, 1989;Stefanini et al, 1995), although other studies suggest that food intolerance is not a major factor in this syndrome (Farah et al, 1985;McKee et al, 1987). Two hypotheses may be formulated: (a) our patients had foodrelated IBS with particularly severe intestinal motor derangement, although they did not ful®ll criteria for IBS but rather those for functional diarrhea, a separate entity (Drossman et al, 1990); (b) intestinal dysmotility is a feature of food intolerance, whose expression may be similar to other`irritative' or`allergic' small bowel reactions related to particular foodstuffs in a given subject.…”
Section: Considerationsmentioning
confidence: 95%
“…An 8-week treatment with sodium cromoglycate significantly improved symptoms in the first study [16], but only about 30 % of patients reported a significant decrease of stool frequency after a 4-week regimen in the second study, with no improvement in the placebo group [17]. The largest uncontrolled study (n = 409) compared a 1-month course of sodium cromoglycate with an elimination diet, reporting comparable results with both interventions in decreasing IBS related symptoms [18]. Response rates in both groups may have been better for patients with positive skin tests for dietary antigens; however, the lack of a placebo group limits interpretation of these data.…”
mentioning
confidence: 97%
“…More recently, a subset of IBS-d patients with increased intestinal MC identified in biopsy specimens have been reported to respond well to MC stabilizers termed ''mastocytic enterocolitis'' [13]. A handful of clinical trials have also reported symptomatic improvement in IBS treated with MC stabilizers [14][15][16][17][18][19][20]. The association between MC and diarrhea/abdominal cramps, is further highlighted by the fact that these symptoms are prevalent in patients with intestinal involvement by systemic mastocytosis [21,22].…”
mentioning
confidence: 99%
See 1 more Smart Citation